Carbon and nitrogen metabolic regulation in freshwater plant Ottelia alismoides in response to carbon limitation: A metabolite perspective - Huang, Wenmin; Han, Shijuan; Wang, Liyuan; Li, Wei (Frontiers in Plant Science, 2022)
Carbon and nitrogen metabolism are basic, but pivotal metabolic pathways in plants and are tightly coupled. Maintaining the balance of carbon and nitrogen metabolism is critical for plant survival. Comprehensively revealing the metabolic balance of carbon–nitrogen interactions is important and helpful for understanding the adaptation of freshwater plants to CO2 limited aqueous environment. A comprehensive metabolomics analysis combined with physiological measurement was performed in the freshwater plant Ottelia alismoides acclimated to high and low CO2, respectively, for a better understanding of how the carbon and nitrogen metabolic adjustment in freshwater plants respond to carbon limitation. The present results showed that low CO2 acclimated O. alismoides exhibited significant diurnal titratable acidity and malate fluctuations, as well as an opposite diel pattern of starch change and high enzymatic activities required for crassulacean acid metabolism (CAM) photosynthesis, which indicates that CAM was induced under low CO2. Moreover, the metabolomic analysis showed that most intermediates of glycolysis, pentose phosphate pathway (PPP) and tricarboxylic acid (TCA) cycle, were increased under low CO2, indicative of active respiration in low-CO2-treated O. alismoides. Meanwhile, the majority of amino acids involved in pathways of glutamate and arginine metabolism, aspartate metabolism, and the branched-chain amino acids (BCAAs) metabolism were significantly increased under low CO2. Notably, γ-aminobutyric acid (GABA) level was significantly higher in low CO2 conditions, indicating a typical response with GABA shunt compensated for energy deprivation at low CO2. Taken together, we conclude that in low-CO2-stressed O. alismoides, CAM photosynthesis was induced, leading to higher carbon and nitrogen as well as energy requirements. Correspondingly, the respiration was greatly fueled via numerous starch degradation to ensure CO2 fixation in dark, while accompanied by linked promoted N metabolism, presumably to produce energy and alternative carbon sources and nitrogenous substances for supporting the operation of CAM and enhancing tolerance for carbon limitation. This study not only helps to elucidate the regulating interaction between C and N metabolism to adapt to different CO2 but also provides novel insights into the effects of CO2 variation on the metabolic profiling of O. alismoides.